2021
DOI: 10.14421/joyced.2021.12-06
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Development of Children Aged 4-7 Years During The Covid-19 Pandemic

Abstract: Cognitive development is one aspect of child development that is very important to get intervention during the COVID-19 pandemic,  Cognitive development is a development that is closely related to thinking skills, such as reasoning, memory, and the ability to solve practical problems. The cognitive mindset of early childhood is very much different from people who are teenagers and adults or even children who are in middle school and above. Elementary school age children have limitations in thinking about abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In addition to those mentioned above, similar correlations were obtained between leisure activities and family-school relationship; co-responsibility and family-school relationship, and emotional impact and academic performance. The results are supported by evidence that the family-school relationship is an indicator of family involvement in the educational process, which is generalized in other informal educational contexts, resulting in higher academic achievement and cognitive stimulation (Oktaviana and Srianggita, 2021). Furthermore, co-responsibility in the family evidences a sense of shared responsibility for education in both formal and informal settings.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to those mentioned above, similar correlations were obtained between leisure activities and family-school relationship; co-responsibility and family-school relationship, and emotional impact and academic performance. The results are supported by evidence that the family-school relationship is an indicator of family involvement in the educational process, which is generalized in other informal educational contexts, resulting in higher academic achievement and cognitive stimulation (Oktaviana and Srianggita, 2021). Furthermore, co-responsibility in the family evidences a sense of shared responsibility for education in both formal and informal settings.…”
Section: Discussionmentioning
confidence: 56%
“…Younger students usually receive more one-on-one attention from adults and are supervised more. Consequently, the quality and frequency of interactions between parents and children is more conducive to children's development by creating a motivating and stimulating learning environment (Oktaviana and Srianggita, 2021). Small effect sizes were shown in the other variables, whose direction showed greater resilience in Early Childhood Education students during lockdown (Giménez-Dasí et al, 2020;Egan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the COVID-19 pandemic, schools are moving to distance learning using various online learning apps and platforms (Alomyan, 2021). Implementation of distance learning has lasted almost two years, and education practitioners and observers in Indonesia have become concerned about critical students' learning loss (Oktaviana & Srianggita, 2021). Research conducted by the Ministry of Education, Culture, Research, and Technology found that during the pandemic, students experienced a learning loss equivalent to six months and five months for literacy and numeracy, respectively.…”
Section: Learning Loss As a Results Of Online Learningmentioning
confidence: 99%
“…Pemerintah saat ini berupaya menerapkan strategi dan metode pengajaran yang melalui guru-guru pendidikan anak usia dini (Oktaviana & Srianggita, 2021). Strategi dan metode pengajaran dilaksanakan secara daring.…”
Section: Pendahuluanunclassified